2022
DOI: 10.4103/jfmpc.jfmpc_1594_21
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of liver function tests in severe acute respiratory syndrome - Corona virus 2 (SARS-CoV-2) infection in the backdrop of chronic kidney disease

Abstract: Background: The SARS-CoV-2 pandemic has emerged as the most challenging global health problem of this century. The concomitant presence of co-morbidities like chronic kidney disease (CKD), diabetes, CHD, further complicates the problem. Aim: To assess the patterns of LFT abnormalities in patients of SARS-CoV-2 infection with and without CKD and evaluate the probable outcomes. Materials and Methods: A cross-sectional retrospective observationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Thus, they concluded that elevated ALP values in CKD patients with COVID-19 infection may be used as an indicator of declining kidney function. 32 This contradiction between different studies needs more investigation in future studies. Generally, liver damage can be a result of underlying conditions in these individuals, COVID-19 itself, or the therapeutic interventions performed on these patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, they concluded that elevated ALP values in CKD patients with COVID-19 infection may be used as an indicator of declining kidney function. 32 This contradiction between different studies needs more investigation in future studies. Generally, liver damage can be a result of underlying conditions in these individuals, COVID-19 itself, or the therapeutic interventions performed on these patients.…”
Section: Discussionmentioning
confidence: 97%
“…SARS‐CoV‐2 positive CKD patients were found by Kumar et al to have higher serum aminotransferase levels than their non‐CKD COVID‐19‐positive counterparts, and these levels were significantly correlated with calculated eGFR values. Thus, they concluded that elevated ALP values in CKD patients with COVID‐19 infection may be used as an indicator of declining kidney function 32 . This contradiction between different studies needs more investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%